Faktor-Faktor Penggerak Nilai Perusahaan pada Perusahaan Sektor Consumer Non Cyclicals di BEI : Struktur Modal, Tax Avoidance dan Kebijakan Deviden - Saragih, Muhammad Rizal; Rusdi, Rusdi; Muslim, Muslim (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The value of a company is a crucial indicator reflecting investor confidence and the overall health of a business. In the consumer non-cyclical sector, factors such as capital structure, tax avoidance strategies, and dividend policy play significant roles in shaping company value. This study aims to empirically investigate the influence of capital structure, tax avoidance, and dividend policy on the company value of firms listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. Utilizing a quantitative research approach and purposive sampling, the population comprised 125 companies, of which 20 met the criteria after outlier testing, resulting in 80 data points. Multiple linear regression analysis was performed with a 5% significance level using Eviews 9 software. The results reveal that capital structure, tax avoidance, and dividend policy simultaneously and significantly impact company value. These findings suggest that companies strategically manage their debt levels, tax obligations, and dividend distributions to optimize firm valuation. For investors and corporate managers, understanding these relationships is vital for making informed financial decisions and enhancing shareholder wealth. Furthermore, regulatory bodies may consider these insights to refine policies ensuring market stability and transparency.